As Quybyrycas as a possibility of descolonization from the inside - Klipel, Renata de Oliveira (Revista Desassossego, 2023)
This article seeks to discuss how the dictatorial regime established in Portugal from 1933 to 1974 known as Estado Novo appropriated certain cultural elements such as the figure of Luís de Camões and his epic poem Os Lusíadas, to reinforce and constitute values that would serve as a model for an ideal Portuguese society. As a counterpoint to this appropriation on the figure of Camões as a validation for the implementation of colonies on the African continent (since his work refers to a glorious period in the history of Portugal), António Quadros decides to write the lost continuation of Os Lusíadas, with the aim of disassociating the poet from the imperialist values to which the Estado Novo had conditioned him. We propose, therefore, in this text to analyze the work of Quadros, As Quybyrycas, to perceive how it provides a decolonization movement emerging from the interior of the Portuguese culture.